2013
DOI: 10.1007/s00404-013-2836-6
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary infection prevalence among women who used an intrauterine device or oral contraceptives

Abstract: It is believed that the most significant reason for genitourinary infections among women was inadequate hygiene practices rather than use of different contraception methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…26 A study conducted at Mother and Child Health and Family Planning center in Turkey suggested inadequate hygiene practices as the most significant reason for genitourinary infections among women. 29 This reflects that hygiene plays an important role in combating infections. In India, there is an effort to extend reproductive tract infections treatment services through the formal healthcare system to women seeking family planning and other reproductive health services.…”
Section: Discussionmentioning
confidence: 99%
“…26 A study conducted at Mother and Child Health and Family Planning center in Turkey suggested inadequate hygiene practices as the most significant reason for genitourinary infections among women. 29 This reflects that hygiene plays an important role in combating infections. In India, there is an effort to extend reproductive tract infections treatment services through the formal healthcare system to women seeking family planning and other reproductive health services.…”
Section: Discussionmentioning
confidence: 99%
“…Demirbag et al reported a cross‐sectional study comparing the prevalence and molecular signatures of UTIs between OCP and IUD users in Trabzon, Turkey 23 …”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, criteria for diagnosing a UTI were variable (Table 1). Five of nine studies identified UTI by the presence of a single positive urine culture and/or dipstick, 20,23‐26 while four studies relied on qualitative urinary symptoms 17,18,20,27 17,18,21,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the asymptomatic infections of UU [20] and CT [45] , early and active detection of those infections plays an important role in decreasing the STIs infection. Although routine screening of asymptomatic person or routine testing of symptomatic individuals for UU is not recommended in the European STI Guidelines [46] , the situation of China might be different, especially for the internal migrants of China.…”
Section: Discussionmentioning
confidence: 99%